The impact of digital marketing channels on consumer buying decision / Noor Aslinda Abu Seman and Vicneswaran Segar - Abu Seman, Noor Aslinda; Segar, Vicneswaran (Faculty of Business and Management, 2023)
Recent reports show how Malaysians are increasingly turning to digital channels for purchasing and making decisions. However, some issues that arise in different digital marketing channels, including email marketing, search engine marketing, and social media marketing, can lead to negative consequences such as email overload, misinterpretation of search results, and the spread of false or offensive content. The study aimed to examine the impact of email marketing, search engine marketing (SEM), and social media marketing on consumer buying decisions. The study used a quantitative method, with 384 respondents from the region Johor, Malaysia, surveyed using convenience sampling. The results of the study indicated that email marketing has a negative relationship with consumer buying decisions, whereas search engine marketing and social media marketing have a positive relationship with consumer buying decisions. Therefore, the study recommends that marketers focus on digital marketing channels such as search engines and social media marketing to improve their marketing efficiency since they have a more significant impact on consumer buying decisions compared to email marketing.